Edukasi dan Praktek Senam Sehat untuk Meningkatkan Kebugaran Ibu Hamil di Desa Kedungjaya Kecamatan Kedawung Kabupaten Cirebon - Sofiyati Sofiyati (Compromise Journal Community Proffesional Service Journal, 2025)
Pregnancy is a physiological process accompanied by significant physical and psychological changes in pregnant women. One of the most common complaints, particularly in the third trimester, is back pain and decreased physical fitness. Prenatal exercise is a non-pharmacological method proven effective in improving fitness, reducing discomfort, and preparing both physically and mentally for childbirth. This community service program aimed to enhance the knowledge and skills of pregnant women in Kedungjaya Village, Kedawung Sub-district, Cirebon Regency, through education and practical sessions on prenatal exercise. The method included a 60-minute educational session covering the definition, objectives, benefits, and precautions before performing prenatal exercise, followed by a 90-minute practical session guided by a qualified instructor. The results showed an increase in participants’ understanding of the benefits of prenatal exercise and their ability to implement it independently. This program is expected to improve maternal fitness, reduce physical complaints during pregnancy, and optimize physical and psychological readiness for labor.